Senior Pharmacy Students’ Knowledge and Perception towards Herbal Medicines: A Preliminary study from Malaysia - Hassali, Mohamed Azmi Ahmad; Shafie, Asrul Akmal; Subish, Palaian (Journal of Pharmacy Practice and Community Medicine)
Objectives: This study was to evaluate the perception of senior pharmacy students towards herbal medicines and determine their knowledge towards herbal medicines as well as to identify whether there is any association between the current year of study of the senior pharmacy students and their level of knowledge towards herbal medicines. Methods: Questionnaires which contain 21 items, 6 items in 5 point Likert scale for the perception part while 15 items in limited choices for the knowledge part were distributed to all 3rd year and 4th year senior pharmacy students. The data collected was analyzed by using SPSS software version 12. Results: Most of the respondents gave neutral responses towards the statements that seek for their perspectives in herbal medicines. By the way, the highest portion of respondents (56.4%) was categorized in the intermediate level while the amount of respondents with high knowledge in herbal medicines was ranked the second place among three with a percent of 37.2%. The amount left was in a poor level of knowledge. This study showed that the current year of study was associated with the level of herbal knowledge. Conclusions: Senior pharmacy student knowledge of herbal medicines varies depending on the current year of study in pharmacy program and they were not confident enough in giving perceptions towards herbal medicines. The pharmacy curriculum should be revised in order to enable senior pharmacy students accessing herbal medicines more often and broaden their view and knowledge in that particular field.
Keywords: Herbal medicines; Knowledge; Malaysia; Perception; Senior pharmacy students